Text & Act: Essays on Music and Performance - Taruskin, Richard 1945-2022 (New York Oxford University Press, 1995)
Over the last dozen years, the writings of Richard Taruskin have transformed the debate about "early music" and "authenticity." Text and Act collects for the first time the most important of Taruskin's essays and reviews from this period, many of which now classics in the field. Taking a wide-ranging cultural view of the phenomenon, he shows that the movement, far from reviving ancient traditions, in fact represents the only truly modern style of performance being offered today. He goes on to contend that the movement is therefore far more valuable and even authentic than the historical verisimilitude for which it ostensibly strives could ever be. These essays cast fresh light on many aspects of contemporary music-making and music-thinking, mixing lighthearted debunking with impassioned argumentation. Taruskin ranges from theoretical speculation to practical criticism, and covers a repertory spanning from Bach to Stravinsky. Including a newly written introduction, Text and Act collects the very best of one of our most incisive musical thinkers.
Keywords: Early music; Historically informed performance; Music criticism